beta-Catenin regulates intercellular signalling networks and cell-type specific transcription in the developing mouse midbrain-rhombomere 1 region. - Dmitri Chilov; Natalia Sinjushina; Jonna Saarimäki-Vire; Makoto M Taketo; Juha Partanen (PLoS ONE, 2010)
beta-Catenin is a multifunctional protein involved in both signalling by secreted factors of Wnt family and regulation of the cellular architecture. We show that beta-catenin stabilization in mouse midbrain-rhombomere 1 region leads to robust up-regulation of several Wnt signalling target genes, including Fgf8. Suggestive of direct transcriptional regulation of the Fgf8 gene, beta-catenin stabilization resulted in Fgf8 up-regulation also in other tissues, specifically in the ventral limb ectoderm. Interestingly, stabilization of beta-catenin rapidly caused down-regulation of the expression of Wnt1 itself, suggesting a negative feedback loop. The changes in signal molecule expression were concomitant with deregulation of anterior-posterior and dorso-ventral patterning. The transcriptional regulatory functions of beta-catenin were confirmed by beta-catenin loss-of-function experiments. Temporally controlled inactivation of beta-catenin revealed a cell-autonomous role for beta-catenin in the maintenance of cell-type specific gene expression in the progenitors of midbrain dopaminergic neurons. These results highlight the role of beta-catenin in establishment of neuroectodermal signalling centers, promoting region-specific gene expression and regulation of cell fate determination.